The Association Between Financial Hardship and Mental Health Difficulties Among Adult Wage Earners During the COVID-19 Pandemic in Bangladesh: Findings From a Cross-Sectional Analysis - Sultana, Mst. Sadia; Khan, Abid Hasan; Hossain, Sahadat; Islam, Tauhidul; Hasan, M. Tasdik; Ahmed, Helal Uddin; Li, Zezhi; Khan, Jahangir A. M. (Frontiers in Psychiatry, 2021)
Background: The ongoing COVID-19 pandemic has created several challenges including the financial burden which may result in mental health conditions. This study was undertaken to gauge the mental health difficulties during the COVID-19 pandemic to gain an insight into wage earners’ mental health. Method: This cross-sectional study was conducted through an online survey, a total of 707 individual Bangladeshi wage earners were enrolled in between 20 May 2020 and 30 May 2020. The questionnaire had sections on sociodemographic information, COVID-19 related questions, PHQ-9 & GAD-7 scales. STATA version 14.1 program was used to carry out all the analyses. Results: The study revealed that 58.6% and 55.9% of the respondents had moderate to severe anxiety and depressive symptoms, respectively. The total monthly income less than 30,000 BDT (353.73USD) displayed increased odds of suffering from depressive symptoms (OR=4.12; 95% CI: 2.68-6.34) and anxiety (OR=3.31; 95% CI: 2.17-5.03). Participants who didn’t get any salary, had no income source during pandemic, had financial problem, inadequate food supply were more likely to suffer from anxiety and depressive symptoms (p ≤ .01). Perceiving the upcoming financial crisis as a stressor was a potential risk factor for anxiety (OR=1.91; 95% CI:1.32-2.77) and depressive symptoms (OR=1.50; 95% CI:1.04-2.16). Limitations: Online survey limits the generalizability of the study and self-reported answers might include selection and social desirability bias as community-based survey was not possible during pandemic situation. Conclusion: Wage earners in a low resource setting like Bangladesh require mental health attention and financial consideration to deal with mental health difficulties during this pandemic.